1988
DOI: 10.1148/radiology.168.1.3380972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of acquisition of MR imaging units in an era of prospective payment.

Abstract: A survey was undertaken to examine the impact of Medicare's Prospective Payment System (PPS) and other recent changes in the health care environment on providers' decisions regarding acquisition of high-cost technologic equipment. The survey group included 199 hospitals and freestanding imaging centers known to have acquired magnetic resonance (MR) imaging units, as well as a random sample of 400 hospitals whose acquisition decisions were unknown to the authors. Fifty-eight percent of the known adopters and 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…If the market where hospitals operate has, however, mechanisms in place to restrict and control the use of imaging, then the effect of physician supply and market size on adoption might not be as strong as that in a market without control policies. Examples of these mechanisms include reimbursement rates (and coverage), prior‐authorization requirements, and certificate of need . If stringent, these mechanisms can all reduce the revenue potential that a hospital can expect to derive from adopting a new technology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the market where hospitals operate has, however, mechanisms in place to restrict and control the use of imaging, then the effect of physician supply and market size on adoption might not be as strong as that in a market without control policies. Examples of these mechanisms include reimbursement rates (and coverage), prior‐authorization requirements, and certificate of need . If stringent, these mechanisms can all reduce the revenue potential that a hospital can expect to derive from adopting a new technology.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed and demonstrated positive associations between investments in medical technologies and various measures of hospital performance . The provision of high‐quality care and the enhancement of diagnostic capabilities have been identified as significant factors affecting adopters' decisions to acquire medical technologies in hospitals . Hospitals are becoming increasingly reliant on technology to deliver high quality patient care, and diagnostic radiology, in particular, is recognized to be part of a larger system whose goal is to treat patients effectively and efficiently .…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation